Interacting effect of MAOA genotype and maternal prenatal smoking on aggressive behavior in young adulthood - Hohmann, Sarah; Rietschel, Marcella; Witt, Stephanie; Schmidt, Martin H.; Meyer-Lindenberg, Andreas; Banaschewski, Tobias; Brandeis, Daniel; Laucht, Manfred (Journal of neural transmission, 2016)
Findings on the etiology of aggressive behavior have provided evidence for an effect both of genetic factors, such as variation in the monoamine oxidase A (MAOA) gene, and adverse environmental factors. Recent studies have supported the existence of gene x environment interactions, with early experiences playing a key role. In the present study, the effects of prenatal nicotine exposure, MAOA genotype and their interaction on aggressive behavior during young adulthood were examined. In a sample of 272 young adults (129 males, 143 females) from an epidemiological cohort study, smoking during pregnancy was measured with a standardized parent interview at the offspring’s age of 3 months. Aggressive behavior was assessed between the ages of 19 and 25 years using the Young Adult Self-Report. DNA was genotyped for the MAOA 5′ untranslated region variable number of tandem repeats polymorphism (VNTR). Results revealed a significant interaction between MAOA and smoking during pregnancy, indicating higher levels of aggressive behavior in young adults carrying the MAOA low-expressing genotype who had experienced prenatal nicotine exposure (n = 8, p = .025). In contrast, in carriers of the MAOA high-expressing genotype, maternal smoking during pregnancy had no effect on aggressive behavior during young adulthood (n = 20, p = .145). This study extends earlier findings demonstrating an interaction between MAOA genotype and prenatal nicotine exposure on aggressive behavior into young adulthood. The results point to the long-term adverse effects of smoking during pregnancy on the offspring’s mental health, possibly underlining the importance of smoking cessation during pregnancy. According to the nature of the study (particularly sample size and power), analyses are exploratory and results need to be interpreted cautiously.